Fiscal Policy and Regional Output Volatility: Evidence from Russia. Issue 11 (1st November 2016) - Eller, Markus; Fidrmuc, Jarko; Fungáčová, Zuzana
Abstract : Eller M., Fidrmuc J. and Fungácˇ ová Z. Fiscal policy and regional output volatility: evidence from Russia, Regional Studies. This paper investigates the relationship between fiscal policy and output volatility in Russian regions between 2000 and 2009. Accounting for endogeneity between output volatility and fiscal developments by using system-generalized method of moments (GMM) estimation techniques, the results indicate that discretionary fiscal policy contributes to output volatility and induces macroeconomic instability at the regional level in Russia. This corroborates previous studies using cross-country data. To reduce business cycle fluctuations, it would be necessary to curtail procyclical fiscal activism at the regional level, e.g. via fiscal rules and sound institutions of fiscal federalism.